Catolicismo social y obreros católicos en Ecuador durante la década de 1890 (Estudios) - Vizuete Marcillo, Luis Esteban (2019)
The article examines the French alternative of Catholic social doctrine and its reception in Ecuador at the end of the nineteenth century. First, it summarizes the context of Catholic teaching in Europe and Latin America and identifies Ecuador within the process of expanding the Society of Catholic Worker Circles. Second, it introduces certain aspects of Catholic associations, worker associations, and the workers’ press in nineteenth-century Ecuador. Finally, it explores the development and dissemination of Catholic Worker Circles in Ecuador’s Andean region (sierra) in the 1890s. Both lay people and clergy participated in this process.